Cum își percep oamenii viața la patru ani de la Revoluția română? Nevoia de alternative - Bălașa, Ana (Calitatea Vieții, 1994)
The article contains a synthetical but a comprehensive image of this tremendous need for change perceived by the Romanians after December 1989. The existing links between facts and feelings, expectations and realities, satisfactions and dissatisfactions are evaluated in a direct approach based on the registered results of the inquiries organised from 1990 by the Research Institute of the Quality of Life. The final conclusions of this article is that - most of the Romanians are still confident in their future, in spite of all the difficulties.